The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Sustainable Mobility for Island Destinations 2021
DOI: 10.1007/978-3-030-73715-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Is Cycling an Attractive Transport Solution in a Mediterranean City?

Abstract: By exploiting the opinion of the society in a Mediterranean city, this paper identifies the mechanisms behind utility cycling and determines the aspects of using the bike in cities for daily commuting. This study focused on the assessment of biking as an alternative mode of transport within a typical Mediterranean city in Crete. Limited road safety is the principal reason that hinders 60% of respondents from cycling, and 41% from riding more frequently. The survey results are congruent with this statement, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Redesigning urban spaces to favor active mobility remains a fool-proof way to make mobility more sustainable in Limassol. Corroborating recent research on active mobility in Mediterranean insular cities [80], this study found that the lack of infrastructure and traffic safety were among the main causes hindering a more frequent use of walking and cycling. Regarding infrastructure, the extension of pedestrian-only and bicycle lanes is residual, the infrastructure is disconnected and sparse.…”
Section: Discussionsupporting
confidence: 66%
“…Redesigning urban spaces to favor active mobility remains a fool-proof way to make mobility more sustainable in Limassol. Corroborating recent research on active mobility in Mediterranean insular cities [80], this study found that the lack of infrastructure and traffic safety were among the main causes hindering a more frequent use of walking and cycling. Regarding infrastructure, the extension of pedestrian-only and bicycle lanes is residual, the infrastructure is disconnected and sparse.…”
Section: Discussionsupporting
confidence: 66%